2021
DOI: 10.3390/ijms22094297
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase Inhibition Alters Proliferative, Migratory, and Invasive Properties of Human Glioblastoma Cells In Vitro

Abstract: Prostaglandin E2 (PGE2) is known to increase glioblastoma (GBM) cell proliferation and migration while cyclooxygenase (COX) inhibition decreases proliferation and migration. The present study investigated the effects of COX inhibitors and PGE2 receptor antagonists on GBM cell biology. Cells were grown with inhibitors and dose response, viable cell counting, flow cytometry, cell migration, gene expression, Western blotting, and gelatin zymography studies were performed. The stimulatory effects of PGE2 and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Our findings also show that NS398 was able to overcome TMZ-induced overexpression of β-catenin, MGMT, and SOX-2 in T98G, thus confirming the key and the hierarchically superior role played by the COX-2/PGE2 system in the cascade of pathways activated by TMZ and implicated in chemoresistance. NS398 has been one of the earliest COX-2-selective inhibitors discovered [54] and, even if not yet approved by the FDA for clinical use, it continues to be largely used, also recently, by a plethora of researchers, as a prototype COX-2 inhibitor for in vitro and in vivo studies on several types of cancers, including GBM [20,36,55,56]. For our group, in particular, the present work represents a continuation of previous studies showing the ability of NS398 to influence the biology of GBM cell lines as well as the relative derived-neurospheres [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings also show that NS398 was able to overcome TMZ-induced overexpression of β-catenin, MGMT, and SOX-2 in T98G, thus confirming the key and the hierarchically superior role played by the COX-2/PGE2 system in the cascade of pathways activated by TMZ and implicated in chemoresistance. NS398 has been one of the earliest COX-2-selective inhibitors discovered [54] and, even if not yet approved by the FDA for clinical use, it continues to be largely used, also recently, by a plethora of researchers, as a prototype COX-2 inhibitor for in vitro and in vivo studies on several types of cancers, including GBM [20,36,55,56]. For our group, in particular, the present work represents a continuation of previous studies showing the ability of NS398 to influence the biology of GBM cell lines as well as the relative derived-neurospheres [13].…”
Section: Discussionmentioning
confidence: 99%
“…The sulphonamide derivative NS398 is a highly selective COX-2 inhibitor, and even if not yet approved by the Food and Drug Administration (FDA) for clinical use, several studies have reported effective activity on glioma cell lines [20,21]. NS398 has been reported to significantly reduce the proliferation and migration rate and alter the cell cycle phase distribution of GBM cell lines [20,36].…”
Section: Introductionmentioning
confidence: 99%
“…Cell cycle phase was determined by propidium iodide fluorescence detection of 10,000 events in a Guava ® easyCyte flow cytometer (Millipore, Burlington, MA, USA) using a λ ext. of 532 nm for propidium iodide detection [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The most important products of COX-2 activity in cancer processes are prostaglandin E 2 (PGE 2 ) [ 59 ] and prostaglandin E 3 (PGE 3 ) [ 60 ], which are derived from ARA 20:4n-6 and EPA C20:5n-3, respectively. PGE 2 is important in the development of glioblastoma tumors [ 61 , 62 , 63 ] and is associated with radiation resistance [ 62 , 64 ] and TMZ resistance in glioblastoma [ 65 ]. On the other hand, PGE 3 acts as an antitumor agent by reducing the activity of PGE 2 [ 60 ].…”
Section: Synthesis Of Fatty Acids and Glioblastomamentioning
confidence: 99%